Analisis Efisiensi Teknis Usahatani Padi di Kabupaten/Kota Jawa Timur Tahun 2020 - Soleh Hanafi Ihsan; Mohtar Rasyid; Dyah Wahyuningsih (OECONOMICUS Journal of Economics, 2021)
The purpose of this study is to determine the level of technical efficiency of rice farming in East Java districts/cities in 2019-2020. The results show that there are 27 regencies/cities or around 71.05 percent of the total, while in this study there are 11 regencies/cities or about 28.94 percent of the inefficient rice farms that have been efficient in using inputs. The results of the analysis show that rice farming in districts/cities in East Java is in a position to increase its return to scale, which is in a position where the increase in output is greater than the increase in inputs.